On Atheist Spirituality - Crocker, Geoff (Journal for the Study of Spirituality, 2015)
The author of this article has created an inclusive website devoted to an exploration of the meaning of spirituality for atheists'. The article draws on his studies in this field as well as his own developing ideas. Its purpose is to open up these ideas for wider debate.